LOOKING WITH DIFFERENT EYES: UN-WALKING THE DOMINANT DISCOURSE TO COME OUT OF THE CLOSE - Gómez Hincapié, Martha Lucía (2022)
This article presents the pastoral experience of the Colombian Methodist Church, Príncipe de Paz (Prince of Peace), in the city of Bogotá, Colombia. It aims to explore their biblical/theological and pastoral work, in order to propose an inclusive pastoral approach from the perspective of gender and sexual diversity. Phenomenological research is used with a qualitative emphasis that allows us to understand the perceptions of the people who participate in the socio-pastoral phenomenon that is intended to be addressed. The results show the pastoral strategies that are inclusive in nature that, although they are not systematized, are made visible through the experiences narrated by their members. As well as the implementation of liberating hermeneutics and the need to move towards transformative pedagogical mediations that consolidate these inclusive pastoral processes.